Respuesta :

Answer: (3,-2)

Step-by-step explanation:

[tex]-3x-7y=5\\15x+6y=33[/tex]

[tex]5(-3x-7y)=5(5)\\-15x-35y=25[/tex]

new system:

[tex]-15x-35y=25\\15x+6y=33[/tex]

add.

[tex]-29y=58\\y=-2[/tex]

plug in -2 for y

[tex]-3x-7(-2)=5\\-3x+14=5\\-3x=-9\\x=3[/tex]

system:

[tex](3,-2)[/tex]

Answer:

(3, - 2 )

Step-by-step explanation:

- 3x - 7y = 5 → (1)

15x + 6y = 33 → (2)

multiplying (1) by 5 and adding to (2) will eliminate x

- 15x - 35y = 25 → (3)

add (2) and (3) term by term to eliminate x

0 - 29y = 58

- 29y = 58 ( divide both sides by - 29 )

y = - 2

substitute y = - 2 into either of the 2 equations and solve for x

substituting into (2)

15x + 6(- 2) = 33

15x - 12 = 33 ( add 12 to both sides )

15x = 45 ( divide both sides by 15 )

x = 3

solution is (3, - 2 )